Some Characteristic of Termitaria Soils in Relation to their Surroundings in New Forest Estate, Dehra Dun - Banerjee, S. P.; Mohan, S. C. (Indian Forester, 1976)
The study was conducted to determine the characteristics of termite-Roils in relation to the soils of the surrounding and to know whether the termite-soils originate from the top soil or the subsoil. The termite-soils are characterized by higher proportion of finer fractions-clay and silt, higher organic matter and total nitrogen, better water holding capacity, higher base status, exchange capacity, pH, and total CaO and MgO as compared to the surrounding soils. Quantitatively total K2O is considerably lower than the surrounding top soils as well as subsoils, and total P2O5 is at par with the subsoil but higher than the top soil. The available traction or K20 is almost equal in the inner mass of the termite- soil and the subsoil but higher than the outer crust and the top soil.